Committee 'A' on Draft Fifth Five Year Plan (Policy, Resources and Allocations) Synopsis of Proceedings - Planning Commission (Planning Commission, 1974)
The Chairman referred to the sad demise of Shri Kamal Nath Tewari, Chairman of the Estimates Committee on the evening of January 17, 1974. The Committee adopted a condolence resolution mourning the death of Shri Tewari and adjourned without transacting any business as a mark of respect to the departed soul. At the outset the Chairman briefly outlined the scope of discussions in the Committee with reference to the main subjects which were: basic plan objectives, policy frame, resource mobilisation and allocations to different sectors. The Members would generally express their views with reference to those particular aspects of the draft Fifth Plan. They would neither take any decisions nor arrive at any conclusions. A synopsis of the proceedings would be prepared and submitted to Parliament so that the views expressed by the Members in the Committee were made known to the other Members of Parliament, and the Planning Commission.
Synopsis of Proceedings
Government of India